Human capital among other key factors that promote Performance of Government Aided Primary Schools in Isingiro district, Uganda - Mujuni, Perez Mbiire Batwine; Mwesigye, Adrian R.; Kazooba, Charles Tushabomwe (International Journal of Current Research, 2022)
The purpose of this research was toestablish the relationship between human capital as one of the key factors and performance of government aided primary schools in Isingiro district, Uganda. A cross sectional research design and post post-postivity paradigm used to collect data from 118 government aided primary schools in Isingiro district, Uganda where 475 respondents participated in the study. The study used closed-ended questionnaires, interview guide and checklists. The schools to be included were selected using simple random sampling and were considered as unit of analysis while the respondents who included District officials, head teachers, teachers and school management committee members formed the unit of enquiry, these were selected purposively based on the knowledge they had on subject matter. Each school selected, provided the information from the respondents who in this case were the head teacher, two (2) teachers and a chairperson of school management committee member. The research was guided by the null hypothesis, Ho1: Human capital has no relationship with performance of government aided primary schools in Isingiro district, Uganda assuming other factors constant. The findings of the study revealed a constant significant relationship between human capital issues and performance of government aided primary school at 99% level of confidence (r=.385, p<.01), thus rejecting the null hypothesis (Ho1). The results signify primary schools in Isingiro district, Uganda. The Unique contribution of this studywas, to suggest to planners and managers of government aided primary schools that, since human capital is important for the improvement of primary school performance, it is advisable that the government should impose the human capital law for government aided primary school teachers which possibly caters for teachers’ productivity when given some due care and attention. In addition, the Ministry of Education & Sports should create social benefits for government aided primary school teachers as a means to enhance their wellbeing and motivate them. Moreover, it is also recommended that government aided primary schools’ teachers be given some training and professional workshops to increase their experience and productivity which could probably motivate them and hence perform better at schools.
Keywords: Human capital; Performance; Government Aided Primary Schools; Isingiro District; Uganda